Contemporary Developments and Perspectives in International Health Security - Volume 2 2021
DOI: 10.5772/intechopen.96820
|View full text |Cite
|
Sign up to set email alerts
|

Which Plagues are Coming Next?

Abstract: Plagues and pandemics are no longer distant thoughts of the past. Previously referred as moments in history, infectious diseases have re-emerged as potential existential threats to mankind. International Health Security researchers have repeatedly warned society about impending pandemics and in 2020, the world experienced its first major pandemic in over a century. The SARS-CoV-2/COVID-19 pandemic came fast and hit hard, impacting the entire world within months of discovery. Although SARS-CoV-2 was a completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 150 publications
(355 reference statements)
0
1
0
Order By: Relevance
“…Recent data indicated that arthropod vectors such as mosquitoes or ticks, can carry more than one pathogen, leading to the co-transmission of diseases through one bite. This highlights the importance of VBVDs as a concern to public health [6]. Furthermore, while VBVDs are transmitted by a main vector, secondary vectors such as rodents often can transmit the same pathogens as insects, leading to multiple routes for infection [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data indicated that arthropod vectors such as mosquitoes or ticks, can carry more than one pathogen, leading to the co-transmission of diseases through one bite. This highlights the importance of VBVDs as a concern to public health [6]. Furthermore, while VBVDs are transmitted by a main vector, secondary vectors such as rodents often can transmit the same pathogens as insects, leading to multiple routes for infection [7].…”
Section: Introductionmentioning
confidence: 99%